2019
DOI: 10.1097/iop.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of Free Skin Grafts Overlying Modified Hughes Tarsoconjunctival Flaps Monitored Using Laser-Based Techniques

Abstract: Purpose: It has recently been shown that the flap pedicle does not supply blood to a tarsoconjunctival graft in the modified Hughes procedure in patients. This raises questions concerning the rate of revascularization of the free skin graft commonly used to reconstruct the anterior lamella. The aim of this study was, thus, to monitor the course of revascularization in free skin grafts overlying modified Hughes tarsoconjunctival flaps, using laser-based techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Free skin grafts are known to survive well in the well-perfused periocular area, as shown in our previous studies on free full-thickness skin grafts used on their own to repair defects 14 or in combination with tarsoconjunctival flaps. 15 A flap is often thinned to achieve better reconstructive results, especially in the face. 16 However, flap thinning can compromise the vascular supply of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Free skin grafts are known to survive well in the well-perfused periocular area, as shown in our previous studies on free full-thickness skin grafts used on their own to repair defects 14 or in combination with tarsoconjunctival flaps. 15 A flap is often thinned to achieve better reconstructive results, especially in the face. 16 However, flap thinning can compromise the vascular supply of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of free skin grafts in the well-perfused periocular area is known to be high, as shown in previous studies on free full-thickness skin grafts used on their own to cover defects, 19 or in combination with tarsoconjunctival flaps. 20 Indeed, it is common practice to combine a glabellar flap with other local flaps in cases of very large medial canthal defects, to reduce the length of the flap. For instance, in a case report from 2017, Ogino et al used a glabellar flap, an upper eyelid myocutaneous advancement flap, and a cheek rotation flap to cover a medial canthal defect, while the donor site of the glabellar flap was covered by a Rintala flap.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the authors have shown in previous studies that free full-thickness skin grafts in the periocular area require 7 weeks to become fully reperfused. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTSG is suitable for simple anterior lamellar defects with a healthy orbicularis base [ 7 , 8 ] or for use in combination with vascularized posterior lamellar replacements for bilamellar defects [ 9 , 10 ]. Aesthetically, skin tissues from the ipsilateral or contralateral eyelid, retroauricular, inner brachial, and supraclavicular areas that provide similar color, thickness, and texture are considered ideal donor sites for the periocular region [ 11 ].…”
Section: Anterior Lamellar Defectsmentioning
confidence: 99%